Exploring challenges to medication adherence aacmong young and middle-aged adults with coronary heart disease in China: a qualitative study - Guo, Jianli; Ma, Jian; Xu, Mengqi; Huang, Xiaoli; Ding, Yuan; Zhu, Lingyan; Zheng, Wengui (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAlthough coronary heart disease (CHD) is becoming increasingly common among young and middle-aged adults, their outcomes usually remain suboptimal. One major contributing factor is poor medication adherence. This study aims to explore the challenges they face in maintaining adherence to prescribed medications.MethodsThis was a qualitative study. 27 young and middle-aged adults with CHD (20 men and 7 women) were recruited from a tertiary general hospital in Shanghai between March and May of 2025. Data were collected through semi-structured interviews. An inductive thematic analysis approach was used for data analysis.ResultsTwo themes and four sub-themes were identified in total: (1) Struggling with Illness Identity and Long-Term Medication: Viewing CHD as an acute condition; Suffering from social isolation due to CHD. (2) Taking Medication as an Intruder in Life: Disrupting daily routines due to medications; Experiencing conflicts between medication taking and social responsibility.ConclusionYoung and middle-aged adults with CHD may have difficulty maintaining medication adherence due to distorted illness perceptions, emotional resistance to accepting a chronic condition, and the marginalization of medication-taking within their busy daily routines. These findings highlight the need to explore psychological approaches, such as Acceptance and Commitment Therapy (ACT), as potentially relevant strategies to support illness acceptance and psychological adjustment in this demographic. In addition, nurse-led initiatives that facilitate the integration of medication-taking into daily life warrant further investigation. Future mixed-methods and interventional studies are needed to test the feasibility and effectiveness of these approaches.